A Matter of Time? Measuring Effects of Public Schooling Expansions on Families - Chloe Gibbs; Jocelyn Wikle; Riley Wilson (Institute of Labor Economics (IZA), 2025)
We leverage pronounced changes in the availability of public schooling for young children—through duration expansions to the kindergarten day—to better understand how an implicit childcare subsidy affects mothers and families. Exploiting full-day kindergarten variation across place and time from 1992 through 2022 and novel data on state-level policy changes, combined with a comparison of children of typical kindergarten age to older children, we measure effects on parental labor supply and family childcare expenses. Results suggest that families are responsive to these shifts. Full-day kindergarten expansions were responsible for as much as 24 percent of the growth in employment of mothers with kindergarten-aged children in this time frame.
Keywords: H75; I28; J13; J22; 330; maternal labor supply; kindergarten; public schooling